PENGARUH EARNING PER SHARE (EPS), DEBT TO EQUITY RATIO (DER), RETURN ON EQUITY (ROE), DAN CURRENT RATIO (CR)TERHADAP HARGA SAHAM - Dyah Ernawati; V. Titi Purwantini (AKTUAL, 2018)
This study aims to analyze the influence of Earning Per Share (EPS), Debt to Equity Ratio (DER), Return On Equity (ROE), And Current Ratio (CR) Against Stock Price of Cigarette Companies Listed In Indonesia Stock Exchange (BEI) Year 2009 -2016. Source of data used in this research is secondary data. The sampling technique in this research is using purposive sampling technique. The number of samples used is 4 (four) cigarette companies during the period of 2009-2016. The statistic method used in multiple linear regression by doing the classical assumption test first. The results of this study indicate that EPS, DER, ROE, and CR simultaneously or partially significant effect on stock prices. Coefficient of determination from this research is 56,4% influenced by independent variable while the rest influenced by other variable like ROE and NPM.Keywords: Earning Per Share (EPS), Debt to Equity Ratio (DER), Return On Equity (ROE), Current Ratio (CR) and Stock Price.